The improvement of flexible aerator parameter to increase dissolved oxygen level in freshwater - Md Zain, Badrul Aisham; Anuar, Fatin Farhana; Abdullah Khan, Saad (International Journal of Integrated Engineering, 2020)
Dissolved oxygen is an important requirement for aquatic life. The aerator machine is able to increase the amount of dissolved oxygen in water. A paddle wheel is a widely used aerator machine. A new type of aerator, flexible link aerator, has been introduced to increase the quality of dissolved oxygen in water. To improve the dissolved oxygen level, suitable parameters of flexible link are determined by using MATLAB & Simulink. The width of the flexible link is adjusted from 0.036m to 0.050m while its length is kept constant at 0.55m and 0.65m in two different simulations using MATLAB & Simulink. In terms of dissolved oxygen results, the estimator level displays a constant and stable result for all the combinations of lengths and widths used. In comparison with 0.55m, the 0.65m length of flexible link shows a better result. Based on the simulation results shown, a width of 0.050m and a length of 0.65m present the best parameters for the flexible link manipulator.